Social media and the fragility of Africa - Sylvain Bertelet Ngassam; Simplice Asongu; Gildas Tiwang Ngueuleweu (African Governance and Development Institute (AGDI), 2024)
This research empirically analyzes the effect of social media on fragility. It goes beyond political grounds which oppose techno-optimistic to techno-pessimistic perceptions of the impact of social media to analyze its consequences on global, Security fragility, economic and social fragilities. The research uses annual data from a panel of 47 African countries for the period 2000-2018. Results reveal that the use of social media by the public to organize offline political actions has no outcome on global fragility. However, its use by elites for the same end accentuates global state fragility. This operates through Security and political fragilities. Fragility is negatively associated with higher civil society participation, education and democracy. The use of social media to organize offline political actions either by people or by elites in the context of higher civil society participation reduces fragility, while its use either by people or by elites in the context of higher educational level accentuates state fragility. The use of social media to organize offline political actions by people in the context of democracy boosts fragility but its use by elites in the same framework reduces fragility. There is a need to sensitize people, especially elites in Africa on the threats and opportunities of social media. There is also a necessity to develop a dynamic, well-educated and well-organized civil society and population in order to better valorize the opportunities that social media represents.
Keywords: G20; O38; O40; O55; P37; 330; Social media; state fragility; security fragility; political fragility; economic fragility and social fragilit